Aerobic and Anaerobic Metabolism During Monofin Swimming in Trained Breath-Hold Divers - Ivan Drviš; Dario Vrdoljak; Goran Dujić; Nikola Foretić; Željko Dujić (Journal of Functional Morphology and Kinesiology, 2025)
Background: This study aimed to examine the difference in blood lactate and oxygen saturation between monofin swimming with respiration and with breath-hold diving. The second aim was to investigate the difference between elite and intermediate breath hold-divers. Methods: This study included 15 freediving athletes (five females). Their chronological age was 25.9 ± 2.9 years, body mass 75.5 ± 11.9 kg, and height 180.2 ± 8.9 cm. The sample of variables included anthropometric indices, blood lactate, and oxygen saturation. The participants were measured during 100 m monofin horizontal swimming with respiration and breath-hold diving. Descriptive and inferential statistics were measured. The Kolmogorov–Smirnov (K-S) test was used to determine the normality of distribution. To determine the differences between the groups of participants, the t-test was used to determine the differences in anthropometric indices. Furthermore, to observe the differences between repeated measures, ANOVA with Fischer LSD test was used. Following that, the two-factor ANOVA analysis group (respiration/apnea) and group (intermediate/elite level)) was performed to determine the possible differences between groups in both conditions. Also, Cohen’s effect size was calculated to quantify the differences among the measurements. Results: The results show that the divers perceive significantly smaller levels of lactates during dives with respiration (intermediate, 2.44 ± 0.64 mmol/L; elite, 2.23 ± 0.34 mmol/L) than during apnea (intermediate, 6.06 ± 2.00 mmol/L; elite, 4.10 ± 0.66 mmol/L). Furthermore, intermediate freedivers tend to perceive significantly higher values. Conclusions: To conclude, it can be noted that apnea monofin diving elicits significantly higher lactate production in comparison with distance-matched swimming. Such findings imply the anaerobic nature of breath-holding diving. Apart from that, elite divers tend to show a lower accumulation of lactate. Such findings imply that elite-level divers can endure prolonged apneas with lower anaerobic metabolism use.